Investigating Droidkungfu Android Malware Behaviour Through Static Analysis - Najiahtul Syafiqah, Ismail (2013)
Rapid growth on smartphone user nowadays gives the view that this device becomes necessity on human’s life. Smartphone user expectations is to stay connected with their social networking, managed their daily schedule and also for entertainment purposes. The user friendly interface, ease to use, and offer many sources to download fancy and interesting application from official or alternative market make Android one of the most popular smartphone operating system in this 21st century. The pervasive download application that available in the market without any quality or security control exposed Android user to the malware threat which then will reveal their personal information without user permission. This paper focuses on analysis the behavior of DroidKungFu1 malware by using reverse engineering process to define requirement parameter and find the suspicious permission and risky API flaws of Android application through static analysis technique. At the end of this project, the data collected will used to produce state diagram of DroidKungFu1 and generate attack pattern of DroidKungFu1. This result will help future researcher or student to study on DroidKungFu1 behavior in depth and also give awareness sign to illiterate IT user smartphone on how the malware can affect their personal information.